Analisis Karakteristik Dan Pengaturan Tindak Pidana Ekonomi Dalam Hukum Indonesia Serta Upaya Penyelesaian - Pesman Laia; Hudi Yusuf (CV. ITTC INDONESIA, 2025)
Economic crime in Indonesia is a critical issue that poses a serious threat to the country’s economic stability and undermines public trust in the national financial system. This type of crime encompasses various unlawful practices, including price manipulation, tax evasion, money laundering, and corruption, which not only harm specific individuals or businesses but also have the potential to weaken the overall economic framework. With the rapid advancement of digital technology, perpetrators of economic crimes have become increasingly sophisticated in leveraging modern technology to conceal their illegal activities, such as through cryptocurrency transactions and cross-border dealings that are difficult to trace. Law enforcement efforts face significant challenges, ranging from limited resources and insufficient inter-agency coordination to gaps in public legal awareness. This study aims to identify the characteristics of economic crime in Indonesia, evaluate existing legal regulations, examine enforcement obstacles, and propose strategic measures to enhance the effectiveness of legal actions. The research employs a case study approach, focusing on violations in the banking sector, financial transactions, and consumer rights protection. The findings indicate that improving the effectiveness of economic crime enforcement can be achieved through strengthening law enforcement capacity, updating regulations to be more adaptive to technological changes, utilizing advanced technology, and fostering international cooperation. Close collaboration between the government, law enforcement agencies, and the public is essential in building a more robust and credible legal system, ultimately contributing to sustained national economic stability.